2019
DOI: 10.1016/s1470-2045(19)30329-8
|View full text |Cite
|
Sign up to set email alerts
|

5-year overall survival in patients with lung cancer eligible or ineligible for screening according to US Preventive Services Task Force criteria: a prospective, observational cohort study

Abstract: BackgroundThe US Preventive Services Task Force (USPSTF) recommends lung cancer screening among individuals aged 55-80 years with a 30 pack-year cigarette smoking history and, if they are former smokers, those who quit within the past 15 years. Our previous report found that two-thirds of newly diagnosed patients with lung cancer do not meet these criteria; they are reported to be either long-term quitters (≥15 years since quitting) or from a younger age group (age 50-54 years). We aimed to assess survival out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 26 publications
2
57
0
2
Order By: Relevance
“…Most researchers thought that the phenomenon may be caused by life pressure, living habits, and hormone levels; however, it needs to be further investigated. Luo et al conducted a cohort study that demonstrated that younger and light smoker patients with lung cancer who are not recommended for screening have similar lung cancer survival to those lung cancer patients who meet all the USPSTF screening criteria (64). This study supports our findings that the individuals with low-risk factors should be concerned as well, and the criteria of current lung cancer screening might not be perfect.…”
Section: Discussionsupporting
confidence: 82%
“…Most researchers thought that the phenomenon may be caused by life pressure, living habits, and hormone levels; however, it needs to be further investigated. Luo et al conducted a cohort study that demonstrated that younger and light smoker patients with lung cancer who are not recommended for screening have similar lung cancer survival to those lung cancer patients who meet all the USPSTF screening criteria (64). This study supports our findings that the individuals with low-risk factors should be concerned as well, and the criteria of current lung cancer screening might not be perfect.…”
Section: Discussionsupporting
confidence: 82%
“…According to our knowledge, this is the first ever report that detects stage 0~IV cancers with a 75.0% sensitivity at 97.3% specificity. Therefore, obtained results indicate that the use of 9G test TM Cancer/Lung with LDCT for lung cancer screening can increase stage I cancer detection, which is crucial to improve the currently low 5-year survival rates [46,47]. Hence, these results indicate that the 9G test TM Cancer/Lung test has a high potential to reduce the false-positive rate of LDCT if used in conjunction with LDCT.…”
Section: Discussionmentioning
confidence: 76%
“…It is estimated that more than 50% of lung cancer patients diagnosed with a localized tumor can live longer than 5 years, but only 16% of lung cancer patients are diagnosed at early stages [3]. Once distant metastasis occurs, only 6% of lung cancer patients can survive for 5 years [4]. Tobacco smoking is responsible for the majority of lung cancer cases, while this disease also affects never-smokers, indicating the complicated pathogenesis [5,6].…”
Section: Introductionmentioning
confidence: 99%